Herbal medicines for SOD1G93A mice of amyotrophic lateral sclerosis: preclinical evidence and possible immunologic mechanism - Yang, Jiang-Li; Wu, Jing-Ying; Liu, Jing-Jing; Zheng, Guo-Qing (Frontiers in Immunology, 2024)
Currently, there is no cure or effective treatment for Amyotrophic Lateral Sclerosis (ALS). The mechanisms underlying ALS remain unclear, with immunological factors potentially playing a significant role. Adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA), a systematic review of preclinical studies was conducted, searching seven databases including PubMed, covering literature from the inception of the databases to April 10, 2024. Methodological quality of the included literature was assessed using CAMARADES, while the risk of bias in the included studies was evaluated using SYRCLE's ROB tool. Review Manager 5.4.1 statistical software was used for meta-analysis of the outcomes. The scoping review followed the Joanna Briggs Institute Methodological Guidelines and reporting of this review followed the PRISMA-extension for Scoping Reviews (PRISMA -ScR) checklist to explore the immunological mechanisms of Herbal Medicine (HM) in treating ALS. This systematic review and meta-analysis involved 18 studies with a total of 443 animals. The studies scored between 4 to 8 for methodological quality and 3 to 7 for risk of bias, both summing up to 10.A remarkable effects of HM in ALS mice, including onset time(Standardized Mean Difference(SMD): 1.75, 95% Confidence Interval(CI ) (1.14 ~ 2.36), Z = 5.60, P < 0.01), survival time(SMD = 1.42, 95% CI (0.79 ~ 2.04), Z = 4.44, P < 0.01), stride length(SMD=1.90, 95% CI (1.21 to 2.59), Z = 5.39, P < 0.01) and duration time (Mean Difference(MD)=6.79, 95% CI [-0.28, 13.87], Z=1.88, P =0.06), showing HM's certain efficiency in treating ALS mice. The scoping review ultimately included 35 articles for review. HMs may treat ALS through mechanisms such as combating oxidative stress, excitatory amino acid toxicity, and calcium cytotoxicity, understanding and exploring the mechanisms will bring hope to patients. Individual herbs and their formulations within HM address ALS through a variety of immune pathways, including safeguarding the blood-brain barrier, countering neuroinflammation, impeding complement system activation, mitigating natural killer cell toxicity, and regulating T cell-mediated immune pathways. The preclinical evidence supports the utilization of HM as a conventional treatment for ALS mice. Growing evidence indicates that HM may potentially delay neurological degeneration